English unlimited Elementary - Baigent, Maggie; Tilbury, Alex; Cavey, Chris; Clementson, Theresa; Robinson, Nick; Hendra, Leslie Anne (Cambridge Univ. Press, 2013)
"English Unlimited is a six-level (A1 to C1) goals-based course for adults. Centred on purposeful, real-life objectives, it prepares learners to use English independently for global communication. Through universal topics and activities, and a focus on intercultural competence as a 'fifth skill', this international coursebook helps learners become more sensitive, more effective communicators. Teaching natural, dependable language, and with CEFR goals at its core, it brings real life into the classroom and gives learners the skills and strategies to communicate confidently outside it. The 'Explore' sections provide the extra ingredients for enhancing communicative ability, from further development of speaking skills to independent learning strategies. The English Unlimited Elementary A Combo includes Coursebook units Intro to 7 as well as the e-Portfolio and Self-Study DVD-ROM." (Verlagsinformation)